Human breast tumor slices as an alternative approach to cell lines to individualize research for each patient - Conde, Sandro Jose [UNESP]; Melo Luvizotto, Renata de Azevedo [UNESP]; de Sibio, Maria Teresa [UNESP]; Nogueira, Célia Regina [UNESP] (Lippincott Williams & Wilkins, 2012)
There are several breast cancer experimental models including cell lines, which are commonly used due to ease of handling and storage. However, the continued propagation of cell lines and distribution among laboratories results in genetic drift and distancing from the in-vivo model. Primary organ culture of breast cancer slices may produce biological responses with high standard deviation for different samples, reflecting the heterogeneity of different tumors. Thus, the organ culture model system offers a new perspective to the results obtained in the cell lines and offers an alternative for studies that seek to individualize treatment for each patient, an increasingly prominent concern in current cancer therapy. European Journal of Cancer Prevention 21:333-335 (C) 2012 Wolters Kluwer Health vertical bar Lippincott Williams & Wilkins.
Keywords: 17 beta-estradiol; breast neoplasms; cell culture techniques; cell line; primary tumor slices culture; triiodothyronine; tumor